Perceptions of Institutional Teaching Culture by Tenured, Tenure-track, and Sessional Faculty - Dawson, Debra L.; Meadows, Ken N.; Kustra, Erika; Hansen, Kathryn D. (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur)

(untitled) (Canadian Society for the Study of Higher Education, 2019)
The Institutional Teaching Culture Perception Survey (ITCPS) was used to investigate beliefs of tenured, tenure-track, and sessional faculty members (N=576) about the teaching culture within three large research-intensive universities in Canada. As predicted, we found significant differences between these three groups of faculty members’ perceptions of their institutions’ teaching cultures. Sessional faculty perceived that their universities rewarded effective teaching less than their tenured or tenure-track colleagues. Tenured faculty were less likely than the tenure-track and sessional faculty to believe it was important to encourage, recognize, or assess effective teaching. These results have important implications for the quality of teachingand, ultimately, student learning, as sessional faculty are teaching an increasing number of students and tenured faculty are the primary decision-makers in setting the priorities for their institutions.